Church and communion : an introduction to ecumenical theology - Goyret, Philip, 1956- (Book collections on Project MUSE., 2022)
"This book is about ecumenism, from a Catholic point of view. The first part, chapters 1 and 2, describe the history of divisions within the Church, as well as of the efforts to bring about Christian unity. The second part examines Ecumenism from a systematic theological perspective. This first part takes into account the different factors that led to definitive ruptures within the Church, which usually are not only theological. The second part-chapters three, four and five-offers a systematic theological analysis of unity in the Church, from the point of view of dogmatic theology. The last chapter, about the practice of ecumenism, is also written from a theological perspective, but with more links with life and spirituality. The chapter recalls that ecumenism can never simply remain a set of theological principles, but rather inspires an attitude and action in charity which are essential to the Christian life"--